Job Satisfaction within the Scottish Academic Profession - Melanie E. Ward; Peter J. Sloane (Institute for the Study of Labor (IZA), 1999)
This paper considers job satisfaction in the academic labour market drawing upon a particularly detailed data set of 900 academics from five traditional Scottish Universities. Recent studies have revealed that in the labour force as a whole women generally express themselves as more satisfied with their jobs than men. Our results show that reports of overall job satisfaction do not vary widely by gender. This result is explained through the nature of our dataset, limited as it is to a highly educated workforce, in which female workers are likely to have job expectations comparable to their male counterparts. Ordered probit analysis is used to analyse the determinants of an academic?s overall satisfaction at work as well as satisfaction with promotion prospects, job security and salary. Comparison salary is found to be an important influence on academics? overall job satisfaction although evidence suggests that academics place a lower emphasis on pecuniary relative to non pecuniary aspects of work than other sectors of the workforce.
Keywords: J44; 330; Job satisfaction; academic labour market; gender differences; Arbeitszufriedenheit; Akademische Berufe; Geschlecht; Schätzung; Schottland